Okoljske tožbe - Dacar, Rok (Podjetje in delo, 2025)
The article examines environmental litigation as an increasingly important legal instrument for environmental protection in Slovenia and beyond. It clarifies the distinction between environmental and climate litigation, emphasizing that climate litigation is a special subset of climate litigation focused on combating climate change. Particular attention is paid to landmark foreign and international court decisions such as Urgenda v. the Netherlands, Milieudefensie v. Royal Dutch Shell and KlimaSeniorinnen v. Switzerland that have shaped legal practice towards more effective environmental protection and strengthened the accountability of states and corporations in preventing environmental harm. The article assesses the Slovenian legal framework, noting that civil law generally provides only indirect protection of the environment via individual interests, while administrative regulations (ZVO-2) provide broader possibilities for the protection of public interest. In conclusion, the article underlines the role of environmental litigation as a key instrument for realizing environmental rights and promoting sustainable policies for the benefit of present and future generations.
Keywords: climate litigation; collective actions; človekove pravice; environmental damage; environmental litigation; environmental protection; human rights; klimatske tožbe; kolektivne tožbe; Mednarodno okoljsko pravo; okoljska škoda; okoljske tožbe; Pravni spori; varstvo okolja